2011
DOI: 10.1177/070674371105600104
|View full text |Cite
|
Sign up to set email alerts
|

How Does Electroconvulsive Therapy Work? Theories on its Mechanism

Abstract: This article reviews 3 current theories of electroconvulsive therapy (ECT). One theory points to generalized seizures as essential for the therapeutic efficacy of ECT. Another theory highlights the normalization of neuroendocrine dysfunction in melancholic depression as a result of ECT. A third theory is based on recent findings of increased hippocampal neurogenesis and synaptogenesis in experimental animals given electroconvulsive seizures. Presently, the endocrine theory has the strongest foundation to expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 55 publications
1
88
0
5
Order By: Relevance
“…It proposes that seizure activity in the limbic system induces neurotrophic effects crucial for therapeutic efficacy (Bolwig, 2011). This hypothesis is in line with the preclinically developed notion that stress is associated with neuronal atrophy and reduced neurogenesis (Duman and Aghajanian, 2012), impaired synaptic plasticity, and dendritic arborization in the hippocampus (Sousa et al, 2000), whereas antidepressants and electroconvulsive stimulation (ECS; the animal model of ECT) stimulate neurogenesis (Bolwig, 2011), synaptogenesis, gliogenesis, and angiogenesis (Duman and Aghajanian, 2012;Bouckaert et al, 2014).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It proposes that seizure activity in the limbic system induces neurotrophic effects crucial for therapeutic efficacy (Bolwig, 2011). This hypothesis is in line with the preclinically developed notion that stress is associated with neuronal atrophy and reduced neurogenesis (Duman and Aghajanian, 2012), impaired synaptic plasticity, and dendritic arborization in the hippocampus (Sousa et al, 2000), whereas antidepressants and electroconvulsive stimulation (ECS; the animal model of ECT) stimulate neurogenesis (Bolwig, 2011), synaptogenesis, gliogenesis, and angiogenesis (Duman and Aghajanian, 2012;Bouckaert et al, 2014).…”
Section: Introductionmentioning
confidence: 63%
“…The 'anatomical-ictal hypothesis' (Bolwig, 2011) aims to unify the concepts introduced above by relating hippocampal dysfunction and neuroplasticity to the working mechanism of ECT. It proposes that seizure activity in the limbic system induces neurotrophic effects crucial for therapeutic efficacy (Bolwig, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of the modified ECT procedure, the risk of fractures has decreased, and these are very rare today (12). Several brain areas are believed to be important for the mode of action of ECT, and different theories behind the antidepressant effect have emerged over the years [for review see (13)]. For example, it has been demonstrated that sub-convulsive seizures have inadequate antidepressant effect and that seizures need to be fully generalised in order to be effective (14).…”
Section: Introductionmentioning
confidence: 99%
“…This multimodal mechanism of action might be one explanation for the varied clinical effects of ECT in very different clinical syndromes, such as severe depression and manic psychosis. It might also explain the huge variety of neurobiological changes that have been found in studies of ECT, ranging from enhancing serotonergic transmission and activating the mesocorticolimbic dopamine system, affecting the glutamate to GABA balance, restoring neuroendocrine function (reversal of HPA axis derangement) and changing functional activity in different brain regions (Swartz 2009, Bolwig 2011). The provoked seizure results in a sudden, endogenous initiated, cerebral activity inhibition, which then ends the seizure (ictal suppression).…”
Section: The Neurobiological Understanding Of Ectmentioning
confidence: 99%